2020
DOI: 10.1021/acs.jpclett.0c00503
|View full text |Cite
|
Sign up to set email alerts
|

Pb-Based Perovskite Solar Cells and the Underlying Pollution behind Clean Energy: Dynamic Leaching of Toxic Substances from Discarded Perovskite Solar Cells

Abstract: Toxicants like Pb in lead-based perovskite solar cells (PSCs) may become available to humans through leaching and transport through water, air, and soil. Here, we summarize the potential toxicity of different substances in PSCs and determine the leaching concentration of typical heavy metals used in PSCs through dynamic leaching tests (DLTs). Extraction fluids for the standard toxicity characteristic leaching procedure, synthetic precipitation leaching procedure, and deionized water were used as the DLT leachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 13 publications
0
82
0
Order By: Relevance
“…[ 22,23 ] Although huge experimental successes have been obtained, the poor stability and toxicity of OIHPs have impeded their commercial applications. [ 24,25 ] Lead cations leaked from unencapsulated OIHPs are water‐soluble and can cause non‐negligible harm to water, [ 26,27 ] plants, and the food chain, [ 28 ] which could have an adverse effect on human health. [ 29 ] Furthermore, OIHPs are sensitive to moisture, heat, oxygen, and UV light, [ 9,30,31 ] and halide migration results in severe luminescence shift under intense light or an electric field.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22,23 ] Although huge experimental successes have been obtained, the poor stability and toxicity of OIHPs have impeded their commercial applications. [ 24,25 ] Lead cations leaked from unencapsulated OIHPs are water‐soluble and can cause non‐negligible harm to water, [ 26,27 ] plants, and the food chain, [ 28 ] which could have an adverse effect on human health. [ 29 ] Furthermore, OIHPs are sensitive to moisture, heat, oxygen, and UV light, [ 9,30,31 ] and halide migration results in severe luminescence shift under intense light or an electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Inevitably, the cell performance limitations are now linked with other parameters such as limiting device lifetime, poor moisture stability of the perovskite, and the toxicity of Pb, which could preclude some application areas for the devices [35,36]. While struggling to invest time on the issues mentioned earlier, optics integration commits an excellent value for efficiency enhancement of the PSC.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Su et al (2020) have examined the impact of Pb-leakage on the environment. They have observed that the total organic carbon and chemical oxygen demand analysis signify discarded PSCs could increase the oxygen consumption and may release CO 2 into the environment [116].…”
Section: Toxicity Issuementioning
confidence: 99%